2006
DOI: 10.1038/ni1206-1281
|View full text |Cite
|
Sign up to set email alerts
|

Immunological correlates of protection from HIV infection and disease

Abstract: The recent meeting on "Immune Correlates of Protection from HIV Infection and Disease" examined new data from a variety of preclinical and clinical settings. These new insights may facilitate vaccine design and clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…However, development of a broadly effective HIV-1 vaccine has proven to be a daunting task, due to variability of the virus and the complex mechanism of envelopemediated viral entry, with minimal exposure of broadly sensitive neutralization epitopes and its interference with adaptive immune responses (Desrosiers, 2004;Heeney, 2004; Letvin et al, 2002;. However, despite these obstacles, examples from long-term nonprogressor human cohorts and proof-of-principle studies in non-human primates have revealed that control of virus load and protection from disease can be achieved in different settings (Heeney & Plotkin, 2006;Jin et al, 1999;Mascola et al, 2000;Montefiori et al, 1996;Schmitz et al, 1999). Several lines of evidence suggest that, similar to protection against retroviral infection in mice, an efficacious prophylactic HIV-1 vaccine may need to elicit both humoral and cell-mediated immune (CMI) responses (Desrosiers, 2004;Heeney, 2006;Mascola et al, 2005;Messer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, development of a broadly effective HIV-1 vaccine has proven to be a daunting task, due to variability of the virus and the complex mechanism of envelopemediated viral entry, with minimal exposure of broadly sensitive neutralization epitopes and its interference with adaptive immune responses (Desrosiers, 2004;Heeney, 2004; Letvin et al, 2002;. However, despite these obstacles, examples from long-term nonprogressor human cohorts and proof-of-principle studies in non-human primates have revealed that control of virus load and protection from disease can be achieved in different settings (Heeney & Plotkin, 2006;Jin et al, 1999;Mascola et al, 2000;Montefiori et al, 1996;Schmitz et al, 1999). Several lines of evidence suggest that, similar to protection against retroviral infection in mice, an efficacious prophylactic HIV-1 vaccine may need to elicit both humoral and cell-mediated immune (CMI) responses (Desrosiers, 2004;Heeney, 2006;Mascola et al, 2005;Messer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Despite more than two decades of research since the discovery of HIV as the etiologic agent of AIDS, the development of an effective HIV type 1 (HIV-1) vaccine remains an unfulfilled priority. While it is generally accepted that ultimately a prophylactic HIV-1 vaccine should induce both humoral and cellmediated immune responses to a number of different HIV antigens (40,63), envelope-based immunogens capable of inducing broadly neutralizing responses currently are not available (13,79,98). Recent approaches have focused on vaccines capable of inducing potent CD8 ϩ T-cell responses to control the virus load, to reduce transmission, and to slow disease development (26,53).…”
mentioning
confidence: 99%
“…A popular prime-boost regimen is that of DNA priming followed by recombinant poxvirus or adenovirus boosting (Amara et al, 2002;McDermott et al, 2005;Wang et al, 2005). Such prime-boost regimens are able to raise cellular immunity, and this has produced encouraging results with the longsought malaria vaccine (Gilbert et al, 2006;McConkey et al, 2003) and in models of HIV infection (Heeney & Plotkin, 2006). The levels of specific CTL activity in immunized sheep may be improved further if optimal immunization dose, adjuvant, route and interval are investigated (Babiuk et al, 2003;Chaplin et al, 1999;De Rose et al, 2002;Gurunathan et al, 2000;Scheerlinck et al, 2004;Watkins et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is in the late stages of VISNA disease that increased virus load and antigen are seen (Brodie et al, 1992;McNeilly et al, 2007;Narayan & Clements, 1989). With immunodeficiency viruses, control of virus load has been linked to the quality and strength of the antiviral CTL response (Heeney & Plotkin, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation